Charles Mackerras - Simeone, Nigel 1956-; Tyrrell, John 1942- (Boydell & Brewer, 2015)
By the time of his death in 2010 at the age of 84, Sir Charles Mackerras had achieved widespread recognition, recorded extensively and developed into a conductor of major international significance. In addition to areas in which he already had forged a distinctive and definitive profile (Janacek, Mozart, Handel, Sullivan) he revisited - and rethought - much of the standard repertoire. The last thirty years were particularly momentous in the coming to fruition of so many cherished projects: not only the Janacek operas but the Gilbert and Sullivan series, the Mozart operas, the two Beethoven cycles, other projects with the Scottish Chamber Orchestra (Schumann and Brahms at Edinburgh; the outstanding late Mozart) and at the Royal Opera House and the Met.